In Search of Meaning Ludwig Wittgenstein on Ethics, Mysticism and Religion - Arnswald, Ulrich (KIT Scientific Publishing, 2009)
The essays collected in this volume explore some of the themes that have been at the centre of recent debates within Wittgensteinian scholarship. This book is an attempt to express the difficult nature of ethics, mysticism and religion, their problematic status in the modern world, and the possible justifications for ethical and religious commitment. Naturally, it also discusses some of the main ideas of Ludwig Wittgenstein. His very personal and often aphoristic way of writing cannot simply be restated or interpreted. However, his philosophy is in need of interpretation, and interpretations are - as we all know - often rather controversial. The collected contributions aim, therefore, at bringing new insight into the essence of Wittgenstein's ethical and religious beliefs by understanding his concepts of thought and language in a more detailed way. In opposition to what we are tentatively inclined to think, the articles of this volume invite us to understand that our need to grasp the essence of ethical and religious thought and language will not be achieved by metaphysical theories expounded from such a point of view, but by focusing on our everyday forms of expression. The articles have in common an understanding of Wittgenstein as not proposing metaphysical theories, but rather showing us the way to work ourselves out of the confusions we become entangled in when philosophizing. Thus, the authors show from a Wittgensteinian perspective that the standard modern approaches to ethics cannot justify traditional moral beliefs.